2018
DOI: 10.1089/biores.2017.0044
|View full text |Cite
|
Sign up to set email alerts
|

Fatness and Fluctuating Body Weight: Effect on Central Vasculature

Abstract: Weight Cycling (WC) is a prevalent behavior associated with adverse cardiovascular (CV) health. However, a 2010 review on the effects of WC and blood pressure (BP) determined that there was not enough evidence to draw definitive conclusions. Central BP is the principal predictor of CV risk compared to peripheral BP. The influence that WC may have specifically on central BP is unknown. Cross-sectional observation of self-reported history of WC on measures of CV health was undertaken. Seventy-five women complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Animal studies have shown that weight cycling, as defined by weight loss followed by weight gain, is associated with loss of energy hemostasis and a rise in hunger and fall in satiety hormones, leading to adipocyte hyperplasia and maladaptive excess visceral fat accumulation . Human studies have linked weight change to vascular function deterioration and elevated BP via visceral fat accumultion . Epidemiological studies have consistently shown that weight change is likely to increase body fat and is associated with unfavorable metabolic and psychosocial attributes .…”
Section: Discussionmentioning
confidence: 82%
“…Animal studies have shown that weight cycling, as defined by weight loss followed by weight gain, is associated with loss of energy hemostasis and a rise in hunger and fall in satiety hormones, leading to adipocyte hyperplasia and maladaptive excess visceral fat accumulation . Human studies have linked weight change to vascular function deterioration and elevated BP via visceral fat accumultion . Epidemiological studies have consistently shown that weight change is likely to increase body fat and is associated with unfavorable metabolic and psychosocial attributes .…”
Section: Discussionmentioning
confidence: 82%
“…Zeigler et al7 found higher levels of WC were associated with increased laboratory BP values and arterial stiffness, mainly through the mediating impact of increased visceral fat. The current study supports the role of WC on abdominal obesity in that the WC group had a significantly higher waist-to-hip ratio compared to the NWC group.…”
Section: Discussionmentioning
confidence: 99%
“…The data for current study was collected in correlation with previous published work assessing the impact of WC on arterial stiffness 7. Sixty-five healthy, overweight/obese, nonsmoking, weight stable, Caucasian women with a body mass index (BMI) >25 kg/m 2 and age of 25–60 years were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…25 However, results are aligned with the literature on lipids’ differences based on non-pharmacological interventions (eg, diet and exercise) and represent clinically meaningful risks. 26 One potential pathway that is hypothesised is that weight cycling promotes visceral fat accumulation, 27 which thereby leads to greater cardiometabolic risks.…”
Section: Discussionmentioning
confidence: 99%